Motivational interviewing targeting diet and physical activity improves adherence to paediatric obesity treatment: results from the MI Values randomized controlled trial. Issue 2 (14th April 2014) - Bean, M. K.; Powell, P.; Quinoy, A.; Ingersoll, K.; Wickham, E. P.; Mazzeo, S. E.
Summary: Background: Adherence is a challenge in obesity treatment. Motivational interviewing (MI) may promote patient adherence. MI Values is a randomized controlled trial of MI implemented as an adjunct to an adolescent obesity treatment [Teaching Encouragement Exercise Nutrition Support (T.E.E.N.S.)]. Objective: Assess effects of MI Values on T.E.E.N.S. attrition and adherence. Methods: Participants were randomized to MI ( n = 58) or control ( n = 41). At weeks 1 and 10, MI participants had brief MI sessions; controls viewed health education videos. All participants continued with T.E.E.N.S. (biweekly dietitian and behavioural support visits; 3 times per week supervised physical activity). Assessments were repeated at baseline, 3 and 6 months. T ‐tests and chi‐square analyses examined T.E.E.N.S. attrition and adherence by group. Results: Adolescents ( N = 99) were primarily African–American (73%) females (74%); age = 13.8 ± 1.8 years, body mass index percentile = 98.0 ± 1.2. Compared with controls, MI participants had greater 3‐month adherence overall (89.2% vs. 81.0%, P = 0.040), and to dietitian (91.3% vs. 84.0%; P = 0.046) and behavioural support (92.9% vs. 85.2%; P = 0.041) visits, and greater 6‐month adherence overall (84.4% vs. 76.2%, P = 0.026) and to behavioural support visits (87.5% vs. 78.8%, P = 0.011). Conclusions: MI enhanced adherence to this obesity intervention. MI Values is the first study to examine the impact of MI on treatment adherence among obese, primarily African–American adolescents.